Police and Crown Prosecutor Use of Restorative Justice and Diversion for Adults and Youth in a High-Crime Area - Weinrath, Michael (Canadian journal of criminology and criminal justice, 2022)
This research assesses the use of diversion and restorative justice (RJ) referrals by patrol officers and Crown prosecutors in a high-crime urban community. Of interest was the influence on referral of legal factors such as prior criminal history and offence severity and the potential impact of extra-legal factors such as age, gender, and Indigenous ethnicity. Data on 1,000 eligible offenders during a 6-month study period were analyzed. About 15% of eligible cases were referred. Police and Crown were not as aggressive as desirable, with the police passing on some eligible low-severity cases later referred by prosecutors. As prior criminal history increased referrals declined, with a more pronounced impact at the patrol officer level. In bivariate analysis, age, gender, and marital, student, and unemployment status exerted small effects, but these were non-significant in multivariate analysis. No evidence of ethnic disparity was found. Crime types of less serious violence and lower property, as well as prior convictions, had moderate bivariate effects, and these persisted in multivariate analysis. Although most cases referred had a limited criminal history and involved minor crimes, police and prosecutors did refer a few involving serious violent offences and prior convictions, showing potential for greater use of RJ.